Optimisation of a travel agency´s product portfolio using a fuzzy rule-based system - Jadrná, Monika; Macák, Tomáš (Univerzita Pardubice, 2018)
This paper focusses on the use of a fuzzy rule-based system for the tourism area, specifically, the optimisation of production for companies operating in the tourism industry. Many travel agencies and other travel companies operate in the current market, and they not only need to win customers, but also retain them. It is necessary to include everything from the cheapest trip alternatives to expensive luxury destinations, and the best in the respective price ranges must be chosen. In this study, the fuzzy rule-based system was used to evaluate the indefinite information in tourism, which is often difficult to quantify, whether this relates to the sociopolitical situation at the destination, weather or satisfaction with the accommodation services. A correct selection of products can be complicated by the fact that consumers in tourism may intend to both satisfy the same needs and several needs by buying a service. The knowledge base includes the rules for dealing with situations of the different combinations of input criteria to achieve the optimum output. The aim of this work was to design a model for optimising the product portfolios of companies operating in the field of tourism using the fuzzy rule-based system. A further goal was determining the appropriate criteria for performing optimisation.
Keywords: multi-criteria analysis options; expert systems; fuzzy rule-based system; tourism; portfolio; optimisation; C02; M11; R41